Pricing Problems in an Input-Output Approach to Environment Protection - Lowe, Peter D. (The Review of Economics and Statistics, 1979)
W HILST centralists may clamour for direct emission controls and marketeers may favour tax refinements to the price structure of traded goods, their common concern to beat pollution would require of them a practical control policy, namely, a list of emission levels for pollutants or the specific rates of taxes that they would propose. Diligent, but isolated, studies of particularly offensive industries may deflect enquiry away from those unobtrusive production activities with such offenders in their chains of dependent suppliers, so failing to reveal their true pollution status. Partial equilibrium studies will certainly lack the broad comparability which equitable interference by the state demands. The overriding superiority of the input-output approach lies in its systematic description of the environmental and economic repercussions, both direct and indirect, of pollution emission standards and taxes. Using a convenient arithmetic example, Professor Leontief (1970) has shown that the inclusion of pollution generation and its control within an extended input-output model is analytically simple. Pollutants are produced as bi-products of industrial activity, and the aggregate generation of each pollutant is controlled by a specified tolerance limit, without regard for spatial impact. Abatement activities are defined to absorb surplus pollution, at the cost of intermediate (manufactured) inputs and value-added. This present paper arises from the author's work' with the United Kingdom Input-Output model, and seeks to extend Leontief's example, and place his pricing recommendations within a broader context. Although Leontief assumes a economy to facilitate direct solution by matrix inversion, the U.K. model is not essentially square, and its solution requires a choice among alternative techniques of industrial production and pollution abatement and, in broader terms, between economic consumption and pollution. These dilemmas are synthesized by enjoining Gross National Product as the objective criterion to a linear programme. So that Leontief's simple arithmetic might be retained, the same square economy is assumed for numerical purposes, but special investigation is made into the opportunity costs of environment protection, the financial consistency of national accounts, and self-financing pollution taxes.